Gender and authorship trends in rhinology, allergy, and skull‐base literature from 2008 to 2018. Issue 9 (16th March 2021) - Halderman, Ashleigh A.; Rao, Anupriya; Desai‐Markowski, Stuti; Yang, Alex; Luong, Amber U.; O'Brien, Erin; Gray, Stacey T.; Lal, Devyani; Lin, Sandra Y.; Orlandi, Richard; Wise, Sarah K.
Abstract : Background: A recent analysis suggested potential narrowing of the gender gap in research productivity in the field of rhinology. This analysis did not, however, provide insight into how the genders are represented in the rhinologic literature. This study aimed to evaluate 11 years of literature to evaluate for gender differences in authorship position, collaborations, category and content of research, citations, and funding to gain perspective on how gender and authorship has changed over time. Methods: Authorship data for all articles on rhinologic subject matter published between January 1, 2008 and December 31, 2018 in four otolaryngology journals was collected. The gender of authors was determined by protocol. Category and content of research and funding status/source were additionally obtained. Results: Data were collected from 2666 articles. Gender of 14, 510 authors was determined. Female authors accounted for 23% of the overall authors and male authors accounted for 77%. Female first authorship increased significantly over time, but there was no change in female senior authorship. The percentage of female authors steadily increased over time, whereas male authorship decreased slightly. Mixed gender teams were shown to be increasing in frequency. Women published more than expected in basic science and allergy and less than expected in skull base. On funded studies, women were significantly underrepresented as senior authors. Conclusion: This study represents the first assessment of gender differences in the rhinology literature. Areas where female representation can improve include senior authorship, increased involvement in skull base publications, and increased funding.